2016
DOI: 10.1007/s00246-016-1548-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Myocardial Function in Infants with Pulmonary Hypertension: The Role of Tissue Doppler Imaging and Tricuspid Annular Plane Systolic Excursion

Abstract: Transthoracic echocardiography is the most common noninvasive method of evaluating pulmonary hypertension (PH) in infants. Identification of reliable, quantitative indices of myocardial function may enhance the diagnostic value of echocardiography in this population. We hypothesized that pulsed wave tissue Doppler imaging (TDI) and tricuspid annular plane systolic excursion (TAPSE) would be reproducible measurements and would suggest decreased ventricular function, in infants with PH. This retrospective case-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…41 Z-scores for TAPSE in both preterm and term infants have also been derived from populational studies 51,52 and this marker has been described as a reproducible index of RV function in infants with PH (96% intra-observer and 92% inter-observers agreement). 53 With the increasing use of echocardiography for screening, degree of PH at diagnosis may be difficult to interpret when assessing individual patients. Our data suggest that a thorough assessment of RV performance may augment the detection of patients that are at the highest risk for poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Z-scores for TAPSE in both preterm and term infants have also been derived from populational studies 51,52 and this marker has been described as a reproducible index of RV function in infants with PH (96% intra-observer and 92% inter-observers agreement). 53 With the increasing use of echocardiography for screening, degree of PH at diagnosis may be difficult to interpret when assessing individual patients. Our data suggest that a thorough assessment of RV performance may augment the detection of patients that are at the highest risk for poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…FAC in neonates has good inter‐ (93%) and intra‐observer (94%) reliability and reference values in that population have been established 41 . Z‐scores for TAPSE in both preterm and term infants have also been derived from populational studies 51 , 52 and this marker has been described as a reproducible index of RV function in infants with PH (96% intra‐observer and 92% inter‐observers agreement) 53 . With the increasing use of echocardiography for screening, degree of PH at diagnosis may be difficult to interpret when assessing individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…16,23 In addition, a previous study found that TAPSE is a reproducible and reliable method and is decreased in both term and preterm infants with pulmonary hypertension compared with controls. 24 Some authors suggest that TAPSE measurement should be added to fetal heart function assessment because it contributes more to right ventricular dominance and cardiac output in the prenatal period. 16,25 Various studies have found a significant decrease in TAPSE in fetal growth restriction and twin-to-twin syndrome co-existing with fetal hemodynamic and vascular changes.…”
Section: Discussionmentioning
confidence: 99%
“…It is a parameter that increases according to gestational age and fetal weight in healthy fetuses 16,23 . In addition, a previous study found that TAPSE is a reproducible and reliable method and is decreased in both term and preterm infants with pulmonary hypertension compared with controls 24 . Some authors suggest that TAPSE measurement should be added to fetal heart function assessment because it contributes more to right ventricular dominance and cardiac output in the prenatal period 16,25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, most measures reported in this study have been shown to be highly feasible and reproducible in premature infants using specific image acquisition and post-processing data analysis protocols. 24, 30, 41, 55 Lastly, we were unable to account for all variables that may have impacted the EI such as PH medications, positive pressure ventilation and PDAs. The impact of these variables on right heart function and clinical course using serial measures of EI as a potentially useful metric over time is worth future study.…”
Section: Discussionmentioning
confidence: 99%